Clinicopathological spectrum and management of sinonasal masses – A prospective observational study in a tertiary care center - Mohsina Siddique,; Debajit Sarma,; Mridusmita Gohain,; Rupanjita Sangma, (Asian Journal of Medical Sciences, 2024)
Background: Sino nasal mass (SNM) is a common clinical entity in the ENT outpatient department. It affects all age groups. SNMs are mainly non-neoplastic inflammatory polyp, benign tumor, and malignant tumor, out of which inflammatory polyp is the most common entity. Radiological investigation plays a major role in SNM. Surgery is the treatment of choice in almost all cases. Functional endoscopic sinus surgery (FESS) is the most commonly employed approach for surgery. Aims and Objectives: The aim of the current study is to analyze the clinicopathological aspects and enumerate the various management strategies of SNMs in patients attending the department of ENT in a tertiary care hospital in the upper Assam region. Materials and Methods: The present study was conducted in Assam Medical College between May 2022 and October 2023. During the period of this prospective observational study, 100 patients presented with SNMs. Results: Total 100 patients were reviewed, out of which 59 patients were male and 41 females. Overall, the most common affected age group was 31–40 years. Seventy-seven cases were non-neoplastic sinonasal polyps, 16 cases were benign tumors and seven were malignant tumors. Sixty-four patients had undergone FESS, 20 patients had endoscopic sinus surgery with or without medial maxillectomy and eight patients had lateral rhinotomy. Malignant cases were managed by radiotherapy and chemoradiation mainly. Conclusion: Sinonasal polyp is a very common entity among all SNMs. Computed tomography scan is the main diagnostic tool. FESS is the most commonly used surgical procedure with less complication.